Anti-Discriminatory Practice - Thompson, Neil, 1955-; British Association of Social Workers (Basingstoke : Palgrave Macmillan, 2006)
Thompson offers a sound basis for countering discrimination and oppression in social work, using a lucid blend of theory and practice to guide students and professionals through the complexities of promoting equality.
Previous ed.: Basingstoke: Palgrave, 2001.
Published in association with the British Association of Social Workers.
Includes bibliographical references (p. 182-203) and index.
Keywords: Social service; Social workers; Discrimination; Society